2013
DOI: 10.1073/pnas.1218498110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the prostaglandin receptor EP2 following status epilepticus reduces delayed mortality and brain inflammation

Abstract: Prostaglandin E2 is now widely recognized to play critical roles in brain inflammation and injury, although the responsible prostaglandin receptors have not been fully identified. We developed a potent and selective antagonist for the prostaglandin E2 receptor subtype EP2, TG6-10-1, with a sufficient pharmacokinetic profile to be used in vivo. We found that in the mouse pilocarpine model of status epilepticus (SE), systemic administration of TG6-10-1 completely recapitulates the effects of conditional ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
251
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 147 publications
(282 citation statements)
references
References 57 publications
26
251
4
1
Order By: Relevance
“…We have previously shown that, during the 24 h following SE, rodents quickly lose 10-20% of their body weight and then gradually begin to recover in the following days (6,8,39). As expected, animals subject to SE lost ∼13% of their body weight in the 24 h after SE onset, independent of Ccr2 genotype (Fig.…”
Section: Ccr2 Ablation Enhances Weight Regain and Reduces Hippocampalsupporting
confidence: 77%
See 4 more Smart Citations
“…We have previously shown that, during the 24 h following SE, rodents quickly lose 10-20% of their body weight and then gradually begin to recover in the following days (6,8,39). As expected, animals subject to SE lost ∼13% of their body weight in the 24 h after SE onset, independent of Ccr2 genotype (Fig.…”
Section: Ccr2 Ablation Enhances Weight Regain and Reduces Hippocampalsupporting
confidence: 77%
“…These admittedly sparse clinical findings are consistent with the much more extensive animal literature in demonstrating a florid inflammatory response of the brain to SE (5). We and others have provided evidence in animal models of epilepsy that quenching inflammation after SE can provide neuroprotection, prevent BBB opening, alleviate morbidity, and rescue behavioral deficits (6)(7)(8)(9)(10).…”
supporting
confidence: 79%
See 3 more Smart Citations